Computer Based Correlation of the Texture of P63 Expressed Nuclei with Histological Tumour Grade, in Laryngeal Carcinomas - Konstantinos Ninos; Spiros Kostopoulos; Ioannis Kalatzis; Panagiota Ravazoula; George Sakelaropoulos; George Panayiotakis; George Economou; Dionisis Cavouras (Analytical Cellular Pathology)
Background. P63 immunostaining has been considered as potential prognostic factor in laryngeal cancer. Considering that P63 is mainly nuclear stain, a possible correlation between the texture of P63-stained nuclei and the tumor’s grade could be of value to diagnosis, since this may be related to biologic information imprinted as texture on P63 expressed nuclei. Objective. To investigate the association between P63 stained nuclei and histologic grade in laryngeal tumor lesions. Methods. Biopsy specimens from laryngeal tumour lesions of 55 patients diagnosed with laryngeal squamous cell carcinomas were immunohistochemically (IHC) stained for P63 expression. Four images were digitized from each patient’s IHC specimens. P63 positively expressed nuclei were identified, the percentage of P63 expressed nuclei was computed, and 118 textural, morphological, shape, and architectural features were calculated from each one of the 55 laryngeal lesions. Data were split into the low grade (21 grade I lesions) and high grade (34 grade II and grade III lesions) classes for statistical analysis. Results. With advancing grade, P63 expression decreased, P63 stained nuclei appeared of lower image intensity, more inhomogeneous, of higher local contrast, contained smaller randomly distributed dissimilar structures and had irregular shape. Conclusion. P63 expressed nuclei contain important information related to histologic grade.